2018
DOI: 10.1186/s13195-018-0429-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness attenuates age-associated aggregation of white matter hyperintensities in an at-risk cohort

Abstract: BackgroundAge is the cardinal risk factor for Alzheimer’s disease (AD), and white matter hyperintensities (WMH), which are more prevalent with increasing age, may contribute to AD. Higher cardiorespiratory fitness (CRF) has been shown to be associated with cognitive health and decreased burden of AD-related brain alterations in older adults. Accordingly, the aim of this study was to determine whether CRF attenuates age-related accumulation of WMH in middle-aged adults at risk for AD.MethodsOne hundred and seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Consistent with previous findings ( Gray et al, 2020 , Fleischman et al, 2015 ), we found smoking is associated with WMH which were confirmed by both the regression and CSD analyses. These associations between cigarette exposure and WMH were also well established in two large samples from the UK Biobank ( Maillard et al, 2015 , Vesperman et al, 2018 ). Our findings further provide evidence for an association between smoking effects and poorer WM integrity.…”
Section: Discussionmentioning
confidence: 54%
“…Consistent with previous findings ( Gray et al, 2020 , Fleischman et al, 2015 ), we found smoking is associated with WMH which were confirmed by both the regression and CSD analyses. These associations between cigarette exposure and WMH were also well established in two large samples from the UK Biobank ( Maillard et al, 2015 , Vesperman et al, 2018 ). Our findings further provide evidence for an association between smoking effects and poorer WM integrity.…”
Section: Discussionmentioning
confidence: 54%
“…Lower cerebral blood flow is associated with higher WMH volume [38,55]. Further, older middle-age adults who are enriched for Alzheimer's disease risk factors, but who have high CRF, show lower WMH volume than peers with lower CRF [56]. Collectively, exercise-induced improvements in vascular health likely augment cerebrovascular function by improving cerebral circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Although cerebral WM changes are common in aging populations, the degree to which they are associated with cognitive and motor symptoms varies between individuals, and may be mediated by protective factors that influence cerebral reserve such as education (Blume et al, 2017) and cardiorespiratory fitness (Johnson et al, 2012; Vesperman et al, 2018). Parkinson's disease, which causes underlying dysfunction of frontal-striatal circuits, represents a preexisting strike against cognitive reserve.…”
Section: Discussionmentioning
confidence: 99%